Pembentukan Karakter Holistik Melalui Pendidikan Interaktif pada Siswa Sekolah Dasar di Pondok Pesantren At-Tausiyah - Khoirul Wafa; Naily Fauziyah; Moch. Romdon Andreansyah; Zakiyyatul 'Azizah; Achmad Arif Rofiki; Ahmad Muhaimin (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
The cultivation of holistic character in elementary school students is a fundamental component in shaping individuals who are morally, socially, and spiritually grounded. This study aims to describe the effectiveness of interactive educational approaches in fostering character development among elementary students at Pondok Pesantren At-Tausyiah, Blitar. A qualitative descriptive method was employed, involving observation, interviews, and active participation during the character-building program. The activities implemented included inspirational storytelling on heroism to foster nationalism and a “water-carrying game” designed to teach values of cooperation and responsibility. Observational data indicated a high level of enthusiasm and active participation from the students throughout the program. Reflections from the students and interviews with facilitators supported the finding that experience-based learning, educational games, and two-way communication significantly enhance both understanding and practice of character values. Beyond strengthening students' character, the program also fostered a joyful learning environment and strengthened the bond between student facilitators and the participants. The findings affirm that interactive education is an effective strategy for holistic character formation, particularly in Islamic boarding school settings.